Use of humic acids from low-grade metamorphism coal for the modification of biofilms based on polyvinyl alcohol - Lebedev, V. V.; Miroshnichenko, D. V.; Zhang, Xiaobin; Pyshyev, S.; Savchenko, D.; Nikolaichuk, Yu. (My University, 2021)
Humic acids (HA) were extracted from three different samples of low-grade Ukrainian coal. Polyvinyl alcohol (PVA) solutions modified with HA of different origin were obtained, which are planned to be used to obtain biodegradable bactericidal resistant films. Studies of the influence of humic acids on the processes of structure formation in PVA solutions have been carried out, on the basis of which it has been shown that they are due to different nature and characteristics of humic acids: presence or absence of coal residue particles.
Keywords: coal; lignite; humic acids; biodegradable bactericidal resistant films; polyvinyl alcohol